PESANTRENOFOBIA SEBAGAI FENOMENA SOSIAL: (Antara Ketakutan, Misinformasi, dan Krisis Kepercayaan) - Muchammad Machrus Zaman (Pascasarjana Universitas Al-Qolam Malang, 2026)
The phenomenon of pesantrenophobia, or social fear toward Islamic boarding schools (pesantren), has emerged as a new sociocultural symptom in modern Indonesian society. Pesantren, which should ideally function as centers of moral, spiritual, and social formation, are increasingly perceived negatively by segments of the public. In reality, amid the rapid flow of modernization and digital information, pesantren are often portrayed as closed, outdated institutions, even associated with issues of violence and intolerance. This reflects a gap between the ideal role of pesantren as enlighteners of the ummah and the social perceptions constructed in public discourse. This study aims to explore the socio-cultural roots of pesantrenophobia, analyze the role of media and misinformation in reinforcing negative images of pesantren, and identify strategies for reconstructing pesantren’s public image and social communication to rebuild public trust. A qualitative descriptive approach was employed, using Social Construction Theory, Framing Theory, and Social Trust Theory as analytical frameworks. The findings reveal that pesantrenophobia stems from the social distance between modern society and pesantren traditions, the historical legacy of colonial discourse portraying pesantren as conservative entities, and the reproduction of negative imagery through media framing and misinformation. Nevertheless, the study also identifies ongoing efforts to reconstruct pesantren’s image through open social communication, digital transformation of pesantren values, and rebranding of pesantren’s humanitarian and educational roles.